Healthy voices, unhealthy silence : advocacy and health policy for the poor - Grogan, Colleen M. (American governance and public policy., 2007)
Public silence in policymaking can be deafening. When advocates for a disadvantaged group decline to speak up, not only are their concerns not recorded or acted upon, but also the collective strength of the unspoken argument is lessenedùa situation that undermines the workings of deliberative democracy by reflecting only the concerns of more powerful interests. But why do so many advocates remain silent on key issues they care about and how does that silence contribute to narrowly defined policies? What can individuals and organizations do to amplify their privately expressed concerns for polic.